Dracos Art Center March 1985 : Carl Andre, Lynda Benglis, Alighiero Boetti, Jonathan Borofsky, Sandro Chia, Nassos Daphnis, Nicola de Maria, Donald Judd, Anish Kapoor, Sol LeWitt, Robert Morris, Giulio Paolini, Robert Rauschenberg, Alan Shields, David Tremlett, Richard Tuttle. (Athene : Dracos Art Center, 1985)
Carl Andre, Lynda Benglis, Alighiero Boetti, Jonathan Borofsky, Sandro Chia, Nassos Daphnis, Nicola de Maria, Donald Judd, Anish Kapoor, Sol LeWitt, Robert Morris, Giulio Paolini, Robert Rauschenberg, Alan Shields, David Tremlett, Richard Tuttle
Carl Andre, Lynda Benglis, Alighiero Boetti, Jonathan Borofsky, Sandro Chia, Nassos Daphnis, Nicola de Maria, Donald Judd, Anish Kapoor, Sol LeWitt, Robert Morris, Giulio Paolini, Robert Rauschenberg, Alan Shields, David Tremlett, Richard Tuttle, Dracos Art Center, Athene, 4 March - 18 April 1985
boek